Chancen und Limitierungen des Positive Leadership-Ansatzes nach PERMA im Lehrkontext: Eine evidenzbasierte Analyse - Karin Meyer (IU Internationale Hochschule, 2022)
– Sales in the management consulting sector reached a new high in 2019, with the trend weakening slightly in 2020 under conditions of a corona pandemic. Simple concepts and new solutions that promise uniqueness are in demand - even if their effectiveness is often not scientifically proven. Against the background of evidence-based management, the question therefore arises as to whether and what opportunities and limitations the Positive Leadership approach according to PERMA promises in the teaching context. Among the results of the evidence-based brief analysis is that approaches for promoting the well-being of students can be derived. At the same time, it is important to pursue a balanced mix of interventions that focuses not only on positive psychology but also on problem-solving and stress management skills.
Keywords: 650; Positive Psychology; Positive Leadership; PERMA; PERMA-Profiler; Well-Being in Students; stress management